Rheumatoid factor IgM autoantibodies control IgG homeostasis - Nicolò, Antonella; Amendt, Timm; El Ayoubi, Omar; Young, Marc; Finzel, Stephanie; Senel, Makbule; Voll, Reinhard E.; Jumaa, Hassan (Frontiers in Immunology, 2022)
Rheumatoid arthritis is an autoimmune disease characterized by joint inflammation due to autoantibodies targeting multiple self-proteins. Most patients with poor prognosis show elevated titers of IgM antibodies specifically binding to IgG. Such autoreactive antibodies are referred to as rheumatoid factor (RF), however, their biological function and contribution to disease progression remains elusive. We have recently shown that autoreactive antibodies are present in healthy individuals and play an important role in regulating physiological processes. This regulatory mechanism is determined by the class and affinity of the autoreactive antibody, as low-affinity autoreactive IgM neutralizes the recognized autoantigen while high-affinity IgM protects its targets antigen from degradation. Here, we show that RFs possessing a high affinity and mono-specificity to IgG have a stabilizing effect on IgG, whereas low-affinity polyreactive RFs neutralize IgG in vivo. These results suggest that autoreactive IgM antibodies recognizing IgG play a crucial role in regulating IgG homeostasis and that a disbalance between IgM-mediated IgG degradation and stabilization might affect the onset and progression of autoimmune diseases. Consequently, restoring this balance using low-affinity anti-IgG IgM might be a promising therapeutic approach for autoimmune diseases involving autoreactive IgG.